ANALISIS SWOT PADA PERUSAHAAN MULTINASIONAL KENTUCKY FRIED CHICKEN (KFC) - Yulfiswandi Yulfiswandi; Benwanto Ardiyano; Gelasia Gwyneth; Supriyadi Arifin (Jurnal Cakrawala Ilmiah, 2023)
This research was conducted because it has the aim of understanding and knowing the implementation techniques in the KFC (Kentucky Fried Chicken) company strategy. The research was conducted using the SWOT analysis method, with the aim of knowing the four elements, namely strengths, weaknesses, opportunities and threats that exist in PT Fast Food Indonesia. Data collection techniques are used to show the advantages and disadvantages of KFC companies. And the results show that the advantages outweigh the disadvantages. This means that the management of the KFC company has implemented the right strategy in running the business. This of course must be maintained and continuously improved by the management so that this company can still compete with new companies in the same field.